The Effect of Push-Up Exercise and Dumbbell Exercise Overhead The Passing Ability of Volleyball Games of SMPN 20 Makassar Extracurricular Participants - Ishak, Anshari H. P.; Hakim, Hikmad; Sahabuddin, Sahabuddin; Hudain, Muh. Adnan; Bismar, Ahmad Rum (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This researcher aims to determine the effect of push-up exercises and dumbbell exercises on the overhead passing ability of volleyball extracurricular participants at SMPN 20 Makassar. The population in this study were students of SMP Negeri 20 Makassar. A sample of 40 people was taken based on random sampling. The dependent variable of the research is the ability to pass under volleyball. The independent variables are push-ups and dumbbell exercises. The research method is an experimental method with a one-group pretest-posttest research design. The research data were analyzed using paired and unpaired t-test techniques at a significance level of 95%. The results of the study showed that: (1) There was a significant effect of push-up training on the passing ability of volleyball extracurricular participants at SMPN 20 Makassar. The results of testing the data obtained a t-count value of 15.891 and t-table obtained 1.729 and a significance value of 0.000 <α0.05, so these results indicate that there is a significant difference. Because the t-count is greater than the t-table, so Ho is rejected. (2) There is a significant effect of dumbbell training overhead passing ability in volleyball extracurricular participants at SMPN 20 Makassar. The results of data testing obtained a t-count value of 14.311 and t-table obtained 1.729, and a significance value of 0.000 <α0.05, so these results indicate that there is a significant difference. Because the t-count is greater than the t-table, so Ho is rejected. And (3) there is a significant difference in the effect of push-ups and dumbbell exercises on overhead passing abilities in volleyball extracurricular participants at SMPN 20 Makassar. The results of data testing obtained a t-count value of 3.440 and a t-table obtained 2.021, and a significance value of 0.001 <0.05, so these results indicate that there is a significant difference. Because the t-count is greater than the t-table, so Ho is rejected. The magnitude of the increase in the push-up group (average value 16.4500) with dumbbell exercises (average value 13.9000) can be seen from the data with an average difference of 2.5500 points. This shows that push-up exercises can improve passing skills in volleyball games for extracurricular participants at SMPN 20 Makassar compared to dumbbell exercises.